Theoretical principles of studying complex sentence at the nominative level - Олексієнко, Алла Валеріївна; Oleksiienko, Alla (Wydawnictwo Akademii Polonijnej „Educator”, 2020)
The article is devoted to the analysis of theories and systematization of knowledge about a complex sentence at the nominative level. Studying of views, concepts and theories of the sentence confirms the complexity and multifaceted nature. It is highlighted, that a sentence is a complex linguistic sign in which two levels interact and intersect – nominative and communi¬cative, but the main attention is drawn tho the first one. The dialectic in the unity of form and content of a sentence is manifested in the duality of formal-grammatical aspect, which is con¬sidered as the superficial structure of the sentence and known by the linguists as “syntactics”, and semantic-syntactic aspect, which is the deep structure of the sentence or “semantics”. It is determined, that the nominative basis of a sentence is the source of the cognitive function of language, which acts as the matrix by means of which the sentence is transformed into a unit of speech, namely utterance.
Keywords: grammar; theory; coordination; clause; taxis; subordination